AN ELISA FOR QUANTIFICATION OF T84.66, A MONOCLONAL ANTI-CEA ANTIBODY, IN MOUSE PLASMA - Urva, Shweta R.; Yang, Victor C.; Balthasar, Joseph P. (Journal of immunoassay & immunochemistry, 2010)
T84.66 is a monoclonal antibody with high affinity and specificity for tumor-associated carcinoembryonic antigen (CEA). In this work, we have developed an enzyme linked immunosorbent assay to determine T84.66 concentrations in mouse plasma. The assay was validated with respect to precision and accuracy by evaluating the recovery of T84.66 from mouse plasma. The working range of the assay is 25-200 ng/mL, and the limit of quantification is 2.5 μg/mL. Intra-assay recoveries ranged from 90.6 to 97.4%, and intra-assay precision reported as the percent coefficient of variation (CV%), ranged from 4.58 to 12.6%. Inter-assay recoveries were between 92.6 to 98.1% and the CV% ranged from 4.9-6.5%. The assay was tested for possible interference from soluble CEA. Soluble CEA, at concentrations up to 5 ng/mL, did not influence the recovery of T84.66. The assay was applied to study the pharmacokinetics of T84.66 in athymic Fox nu mice.